Ukrainian Labour Migration to Europe During the War: A Review of Current Realities - Oleg M. Yaroshenko; Nataliia O. Melnychuk; Ivan P. Zhygalkin; Nataliia M. Shvets; Viktoriia I. Zholudieva (PORTAL: Journal of Multidisciplinary International Studies)
International migration plays an important role in shaping the global economy, serving as both a source of financial resources for countries and a means of balancing demographic and labour disparities across nations. Labour migration, in particular, is integral to the redistribution of labour and capital, influenced by varying levels of economic development, natural resource availability, and technological progress. While globalisation has facilitated the movement of people and strengthened international cooperation, migration patterns are significantly affected by military conflicts. The ongoing war in Ukraine has intensified these dynamics, prompting a significant outflow of Ukrainian labour to Europe. This review explores the economic, social, and demographic impacts of this migration, analysing its effects on host countries and the complex challenges it poses for Ukraine, particularly regarding demographic stability and post-war reconstruction.